Forces at play: exploring factors affecting the cancer metastasis - Riaz, Farooq; Zhang, Jing; Pan, Fan (Frontiers in Immunology, 2024)
Metastatic disease, a leading and lethal indication of deaths associated with tumors, results from the dissemination of metastatic tumor cells from the site of primary origin to a distant organ. Dispersion of metastatic cells during the development of tumors at distant organs leads to failure to comply with conventional treatments, ultimately instigating abrupt tissue homeostasis and organ failure. Increasing evidence indicates that the tumor microenvironment (TME) is a crucial factor in cancer progression and the process of metastatic tumor development at secondary sites. TME comprises several factors contributing to the initiation and progression of the metastatic cascade. Among these, various cell types in TME, such as mesenchymal stem cells (MSCs), lymphatic endothelial cells (LECs), cancer-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs), T cells, and tumor-associated macrophages (TAMs), are significant players participating in cancer metastasis. Besides, various other factors, such as extracellular matrix (ECM), gut microbiota, circadian rhythm, and hypoxia, also shape the TME and impact the metastatic cascade. A thorough understanding of the functions of TME components in tumor progression and metastasis is necessary to discover new therapeutic strategies targeting the metastatic tumor cells and TME. Therefore, we reviewed these pivotal TME components and highlighted the background knowledge on how these cell types and disrupted components of TME influence the metastatic cascade and the establishment of the premetastatic niche. This review will help researchers identify these altered components' molecular patterns and design an optimized, targeted therapy to treat solid tumors and restrict metastatic cascade.